2017
DOI: 10.5194/bg-2017-429
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling seasonal and vertical habitats of planktonic foraminifera on a global scale

Abstract: Abstract. Species of planktonic foraminifera exhibit specific seasonal production patterns and different preferred vertical habitats. The seasonality and vertical habitats are not constant throughout the range of the species and changes therein must be considered when interpreting paleoceanographic reconstructions based on fossil foraminifera. Accounting for the effect of vertical and seasonal habitat tracking on foraminifera proxies at times of climate change is difficult because it requires independent fossi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 60 publications
(173 reference statements)
0
11
0
Order By: Relevance
“…This observation is also in contrast with the modelled relationship of DH with environmental parameters. This is because the strong relationship between DH and MLD in the model reflects a strong link between MLD and the position of the subsurface chlorophyll maximum, as also noted by Kretschmer et al (2018). This strong link likely results from a bias in the ocean component of the Community Earth System Model (CESM1.2) propagated in PLAFOM2.0.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This observation is also in contrast with the modelled relationship of DH with environmental parameters. This is because the strong relationship between DH and MLD in the model reflects a strong link between MLD and the position of the subsurface chlorophyll maximum, as also noted by Kretschmer et al (2018). This strong link likely results from a bias in the ocean component of the Community Earth System Model (CESM1.2) propagated in PLAFOM2.0.…”
Section: Discussionmentioning
confidence: 81%
“…Finally, we evaluate how PLAFOM2.0 (Kretschmer et al, 2018) captures the observed patterns in N. pachyderma depth habitat. To this end, we assess the relationship between modelled DH of N. pachyderma and SST, SSS, MLD, DCM and chlorophyll concentration for summer months in the geographic area covered by the compilation (Fig.1).…”
Section: Resultsmentioning
confidence: 99%
“…The producers of alkenones are restricted to the photic zone and thus are thus close to the surface. However, for foraminifera, the preferred habitat depth and the depth at which their shells calcify is strongly species dependent and can vary from close to the surface, to the thermocline or deeper (Fairbanks and Wiebe, 1980;Kretschmer et al, 2017). Therefore, the recorded temperature will not necessarily reflect the sea surface temperature (Jonkers and Kučera, 2017).…”
Section: Seasonal and Habitat Bias In The Sensormentioning
confidence: 99%
“…The producers of alkenones are restricted to the photic zone and thus are thus close to the surface. However, for foraminifera, the preferred habitat depth and the depth at which their shells calcify is strongly species dependent and can vary from close to the surface, to the thermocline or deeper (Fairbanks and Wiebe, 1980;Kretschmer et al, 2017). Therefore, the recorded temperature will not necessarily reflect the sea surface temperature (Jonkers and Kučera, 2017).…”
mentioning
confidence: 99%
“…Currently, a constant concentration of the signal carrier is an assumption of sedproxy. Future work will enable climate dependent shifts in habitat and abundance to be modelled by implementing a parametrized response of proxy abundance and export to climate variables (Mix, 1987;Schmidt and Mulitza, 2002;Kretschmer et al, 2017;Jonkers and Kučera, 2017;Roche et al, 2017). An alternative option is to couple sedproxy to the output of ecological models that explicitly resolve the population dynamics of the proxy carrier, such as foraminifera population models (Fraile et al, 2008;15 Lombard et al, 2011).…”
mentioning
confidence: 99%